Recuperação de fósforo a partir de efluente industrial por meio de precipitação como sal de estruvita - Fritz Junior, Denilton da Conceição (2022)
The present work had as objective the process of recovery of a brewery industry through different sources of evaluation, for fluent application in the form of objective struvite. Phosphorus recovery tests were initially carried out on a bench scale at different stages, with the main variables of pH control of the samples and a magnesium reagent mass. In this first phase, the first results of superior phosphorus removal were identified. 8.5 and 9.5 of pH concentration between 8.5 and 9.5 of reagent concentration of 1.5g, provided greater nutrient removal, especially for reagent M. In order to evaluate the parameters from of the optimal tests and the evaluation tests were performed (Jar Test for two reagent levels, pH range, reaction time and rotation speed). Thus, obtaining the best results for the concentration of phosphorus in the effluent with the application of MgO reagent, under conditions of pH 8.5; reaction time of 30 minutes and duration of 80 rpm. From the statement in the present study, it is possible to affirm that under conditions and results, the treatment capacity of fluent and significant found in the nutrient removal and recovery stage can be reached.